Mulheres Negras em Movimento: trajetórias militantes, negritude e comida no Sul do Rio Grande do Sul - Rodrigues, Carolina Vergara (2012)
The growing and current mobilization of black identities in the Black Atlantic has been stimulated by elements, objects and practices that results from are ne wed construction of black culture. Above all, is concerned black references non-traditional related to modernity. Given this statement and its reverberation in more remote areas and regions of the Black Atlantic, the focus of analysis is proposed in this work shows the process of building the blackness of a group of black women from southern Brazil. In the course of the text, we have identified and problematize the elements deployed in affirmation of blackness. Giving special attention to the food sand dishes played by the group of women who have been classified as african gastronomy-among them the "vatapa gaucho fashion" and the quibebe . In parallel, thestudy describes the emergence and consolidation of the black movement and the basics struggle anti-racist site, both linked within the path of militancy of these women-pastoral agents black